Moralities of Drone Violence - Enemark, Christian (Edinburgh University Press, 2023)
Moral uncertainty surrounding the use of armed drones has been a persistent problem for more than two decades. In response, Moralities of Drone Violence aims to provide greater clarity by exploring and ordering a variety of ways in which violent drone use can be judged as just or unjust in various circumstances. The book organises moral ideas around a series of concepts of 'drone violence': warfare, violent law enforcement, tele-intimate violence, and violence devolved from humans to artificial intelligence (AI) technologies. In contrast to the way armed drones tend to be debated narrowly in terms of war and law, this broad-based approach to normative inquiry affords more scope to discern and address the potential for these weapon systems to support moral progress or to generate injustice.